Revisiting global food production and consumption patterns by developing resilient food systems for local communities. (August 2022) - Menconi, M.E.; Giordano, S.; Grohmann, D.
Abstract: The achievement of resilient food systems requires an integrated approach between optimal localization of productions and changes in food consumption and between local evaluations of the food system and global visions. In this regard, we developed a Food Self-Sufficiency Index. The index evaluates food self-sufficiency achievable in a study area where its community chooses between alternative suggested diets, and the food productions are relocalized using crop suitability maps. The index can be used at different geographical scales, from a single rural settlement to regional and country-level, up to worldwide. It revisits the food components of the ecological footprint and biocapacity to build a tool for supporting local institutions' decisions in food planning at different levels. In this paper, we discuss how the FSSI could help in increasing the resilience of food production and consumption systems. The paper outlines these essential points for the improvement of the food resilience of an area that aims to improve its self-sufficiency (i) Improving technical solutions, (ii) Improving the communities' involvement, (iii) Improving agro-biodiversity, and (iv) Using complex system approaches in food planning. The Food Self-Sufficiency Index is a powerful supporting decision tool to achieve all the previous goals. Highlights: The ecological footprint and biocapacity indices help in food sovereignty' evaluation. We outline key points for improving the food resilience of a community. We describe an index for the evaluation of the food self-sufficiency achievable in an area. This index is an essential tool for supporting the decisions of Local Institutions. A resilient food system asks for multi-scalar and multifaceted legal and policy frameworks.